Nel riflesso dissimili a se stessi. Il "Doppio ritratto allegorico" dei coniugi Burgkmair di Lucas Furtenagel tra visione e pensiero - Rossi, Alessandro (Elephant & Castle, 2020)
The Double Portrait of the Burgkmair Spouses by Lucas Furtenagel (Vienna, Kunsthistorisches Museum) is here interpreted as a theoretical object, and in particular as an elaborate exemplification of the way of working of Painting itself. Such modus operandi is embodied by the representation of act of "self-awareness” performed by the two subjects of the portrait, represented by means of a double contrast and a compositional harmonisation. By doing so, the painting simultaneously calls into question two different layers of meaning: on one hand, the mimetic register (the portraits themselves) and the symbolic register (the skulls reflected in the mirror) and, on the other, the figurative and verbal aspects (inscriptions) of the painting. By representing what is visible, the pictorial intelligence alludes to the invisible.